Concise Review: A Comprehensive Analysis of Reported Adverse Events in Patients Receiving Unproven Stem Cell-Based Interventions. (31st July 2018) - Bauer, Gerhard; Elsallab, Magdi; Abou-El-Enein, Mohamed
Abstract : The promise of stem cell (SC) therapies to restore functions of damaged tissues and organs brings enormous hope to patients, their families, loved ones, and caregivers. However, limits may exist for which indications SC therapies might be useful, efficacious, and safe. Applications of innovative therapies within regulatory boundaries and within the framework of controlled clinical trials are the norm in the scientific and medical community; such a system minimizes patient risk by setting a clear and acceptable safety and efficacy profile for new therapeutics before marketing authorization. This careful clinical validation approach often takes time, which patients suffering from terminal or debilitating diseases do not have. Not validated, unproven stem cell interventions (SCI) that promise a working treatment or cure for severe diseases have therefore found their way into the patient community, and providers of such treatments often take advantage of the public's willingness to pay large amounts of money for the misguided hope of a reliable recovery from their illnesses. We conducted a review of scientific publications, clinical case reports, and mass media publications to assess the reported cases and safety incidents associated with unproven SCI. The review also analyzes the main factors that were identified as contributing to the emergence and global rise of the "stem cell tourism" phenomenon.